Moderasi Beragama: Keefektivitas Belajar Mengaji Magrib Di Masjid Al- Muttaqin Desa Tanjung Putus - Sitorus, Rojali; Sari, Puspita; Juarsa, Izkal Dwifa; Nuraini, Afraina; Khairiah, Wapiatul (Jurnal Abdi Mas Adzkia, 2024)
Religious moderation, which refers to the attitude of reducing violence and avoiding extremism in religious practice, is a crucial focus in Indonesia as a country with significant religious and cultural diversity. This study aims to examine the effectiveness of the Maghrib Quran learning program at Al-Muttaqin Mosque, Tanjung Putus Village, in supporting religious moderation. This research employs a qualitative approach with a case study method conducted over one month. Data collection techniques include participatory observation, in-depth interviews with program participants, instructors, and community leaders, as well as document analysis. The data were analyzed using thematic analysis to identify key patterns illustrating the program's contributions to religious moderation. The results indicate that the program not only enhances children's ability to read the Quran but also significantly contributes to instilling the values of religious moderation through social interaction and inclusive learning. Factors such as a conducive learning environment and structured teaching methods play an important role in the program's success. Despite challenges like a limited number of qualified teachers, the program has proven effective in fostering moderate religious understanding from an early age while supporting the village government's efforts to promote religious moderation. This study highlights the importance of community-based religious education in building a harmonious and diverse society